2017
DOI: 10.17722/ijme.v9i2.916
|View full text |Cite
|
Sign up to set email alerts
|

Green Transformational Leadership and Green Performance: The mediating role of Green Mindfulness and Green Self-efficacy

Abstract: To increase the green performance of an organization Green Transformational Leadership is very important. This study mainly focuses the impact on Green Performance of Green Transformational Leadership by considering the mediating effect of Green Self-Efficacy and Green Mindfulness.The study is descriptive and quantitative in nature. Survey questionnaire method was used and data have been collected from 200 respondents by applying simple random sampling technique. After applying required tests on AMOS and SPSS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 23 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Second, characteristics of CEOs can affect strategic choices of corporations based on upper echelons theory [7], and transformational leadership is an important characteristic of CEOs [8], supporting the antecedent role of GTL of CEOs for corporates' adoption of EPSs. Third, past research found that GTL can influence green performance [17][18][19], and green performance is a key source of EPSs [20,21]. Finally, a recent study also points out a possible relationship between GTL and EPSs [22].…”
Section: Green Transformational Leadership Of Chief Executive Officers and Environmentally Proactive Strategiesmentioning
confidence: 99%
“…Second, characteristics of CEOs can affect strategic choices of corporations based on upper echelons theory [7], and transformational leadership is an important characteristic of CEOs [8], supporting the antecedent role of GTL of CEOs for corporates' adoption of EPSs. Third, past research found that GTL can influence green performance [17][18][19], and green performance is a key source of EPSs [20,21]. Finally, a recent study also points out a possible relationship between GTL and EPSs [22].…”
Section: Green Transformational Leadership Of Chief Executive Officers and Environmentally Proactive Strategiesmentioning
confidence: 99%
“…Moreover, with the increasing awareness of the environment, GTL (e.g. Chen and Chang, 2013;Chen et al, 2014;Mittal and Dhar, 2016;Nisar et al, 2017;Singh et al, 2020;Zhou et al, 2018) and GOCB (e.g. Lamm et al, 2013) have been brought to the agenda and took place in the green organizational behaviour literature.…”
Section: Effects Of Green Organizational Citizenshipmentioning
confidence: 99%